Religion and Public Opinion in Britain - Clements, B. author. aut Link
XIX, 280 p.
Keywords: Based on extensive analysis of surveys from recent decades, this book provides a detailed study of the attitudes of religious groups in Britain. It looks at continuity and change in relation to party support, ideology, abortion, homosexuality and gay rights, foreign policy, and public opinion towards religion in public life.